VULNERABILITY ANALYSIS OF FOREST AND LAND FIRE IN MOUNTAINEERING ROUTES OF MOUNT MERBABU, SINDORO AND SUMBING, CENTRAL JAVA - Sari, Novia Mawar; Waisnawa, I Putu Gema Bujangga (KURVATEK, 2023)
Forest and land fires are recurring disasters in Indonesia which can cause severe damage to the forest and land. Factors that cause forest and land fires usually influenced by natural conditions such as land cover conditions, soil types, and climatic factor such as the El-Nino phenomenon which can cause long drought, affecting vegetations and have the potential to catch fire when exposed to fire. Human factors such as negligence in activities, in other hand can also cause forest and land fire. Vulnerability analysis in this research is carried out spatially by combining all the components that make up the vulnerability, where each component of the vulnerability is also obtained from the results of combining several parameters. This research is directed to examine the vulnerability in the research area (the climbing route of Mount Merbabu, Sindoro and Sumbing) and draw conclusions in terms of Potential Economic Losses, Potential Environmental Losses and Vulnerability Classes in the research area. The importance of efforts to preserve the environment of these mountains is the responsibility of all of us, especially nature activists so this marvelous environment can be passed on to the next generation. This is in line with one of the Indonesia’s Sustainable Development Goals (SDGs), ensuring that by 2030 everyone has awareness of sustainable development and live an environmentally-sound lifestyle.